Spectroscopic and positron lifetime measurements of hydrogenated single walled carbon nanohorns. Issue 9 (27th April 2016) - Budziak, Andrzej; Dryzek, Jerzy; Juszyńska‐Gałązka, Ewa; Krawczyk, Jan; Parlińska, Magdalena; Wójcik, Dominik; Cios, Grzegorz
Abstract : The hydrogenated and non‐hydrogenated single walled carbon nanohorns (SWCNH) are studied. SWCNH with the density of 0.75 g cm −3 showed the maximum differential hydrogen uptake capacities of 1.4 wt.% at 77 K. The temperature Fourier transform infrared (FT‐IR) spectra for non‐hydrogenated and hydrogenated samples revealed differences in the vibrational mode bands. The hydrogenation of SWCNH hardly affected the positron lifetime spectra. Only small shift of pattern was observed in the X‐ray diffraction measurements at 300 K. Obtained results were compared to these for other carbon nanomaterials.